The effect of nitrogen dilution on flammability limits of LPG - Noraya, Mohd Kadir (2010)
Many manufacturing processes involve flammable chemicals, and an accident involving a fire or an explosion can occur in storage or process equipment if a flammable chemical exist inside it or if a loss of containment of flammable chemicals occurs. The aims of this study are to determine the flammability limits of LPG/ air mixture and to investigate the effect of nitrogen dilution on flammability limits of LPG/ air mixture at atmospheric pressure and ambient temperature. The experiments were performed in a 20 L closed explosion vessel. The mixtures were ignited by using spark permanent wire that placed at the centre of the vessel. The explosion pressure data is used to determine the flammability limits which flame propagation is considered occurred if explosion pressure greater than 0.1 bar. In this study, the result shows the flammability limits of LPG is from 2 % volume to 6 % volume of LPG and have revealed that the addition of nitrogen in LPG/air mixture reduce the upper flammability limit initially 6 % volume to 5 % volume of LPG.